Factors related to parent’s participation in child dental health care in Tegallalang I Public Health Centre - Vivin Sumanti; I Ketut Tangking Widarsa; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2013)
The public health centre reports showed that the level of parent’s participation in children dental health care in Tegallalang I Public Health Centre was low (31.7%-35.1%). This study aims to determine the relationship between parent’s knowledge, attitudes, motivation and transportation accessibility to parent’s participation in child dental health care in Tegallalang I Public Health Centre. A cross-sectional study was conducted to 100 parents whose children were referred to undergo dental health examinations in Tegallalang I Public Health Centre using a systematic random sampling method. Data of knowledge, attitudes, motivation and transportation accessibility were collected using an interview guide, while parent’s participation was obtained from dental care registration. The data were analised by logistic regression. The results showed that level of parent’s participation in child dental health care was low (41%). Variables that were significantly associated with level of parent’s participation in child dental health care were knowledge [OR=7.35; p=0.001], motivation [OR=4.89; p=0.028] and attitudes [OR=4.19; p=0.039). Transport accessibility was not associated with parent’s participation [OR=2.35; p=0.123]. The conclusion of this study is that parent’s participation in child dental health care was influenced by parent’s knowledge about oral health, motivation and attitudes towards child dental health care. It is recommended to upscale health promotion related to dental health and the benefits of treatment in order to encourage parent’s participation in children dental health care.